The Burden of Early Childhood Caries in Canadian Children and Associated Risk Factors - Pierce, Andrew; Singh, Sarbjeet; Lee, JuHae; Grant, Cameron; Cruz de Jesus, Vivianne; Schroth, Robert J. (Frontiers in Public Health, 2019)
Introduction: Early childhood caries (ECC) is any caries in the primary dentition occurring in children under the age of six. ECC is common in many population groups in Canada. Objective: The purpose of this review was to describe the burden of ECC in Canada, the prevalence and associated risk factors for ECC, and its impact on childhood health based on the existing published literature. Methods: A review was conducted to assess published Canadian studies on ECC identified through searches of electronic databases. Databased searched included PubMed, Medline, Cinahl, and the library catalog of the University of Manitoba. Known publications on ECC that were not identified by the electronic search were also considered. Only the studies that reported the prevalence of ECC or caries in preschool aged children were considered. In-depth assessments were restricted to those studies that employed logistic regression analysis to investigate relationship between ECC and risk factors or nutritional status and quality of life. Results: A total of 36 studies were identified that related to ECC in Canadian children. Overall, 27 related to prevalence and 12 reported on risk factors, four related to the association between severe ECC and nutritional health and well-being, while only one related to the oral microbiome composition. Published studies reveal that the prevalence of ECC can be as high as 98% in some parts of Canada. Commonly identified risk factors include age, sex, socio-economic status, parental beliefs, family characteristics, debris/plaque, enamel hypoplasia, and behavioral (oral health or feeding behaviors) tendencies. Conclusions: Current literature reveals that many Canadian children are affected by ECC. The development of ECC appears to be strongly associated with social determinants of health including low household income and the level of parental education or employment status. Associations were also observed between ECC and the child's age at first dental visit and parental beliefs about child's oral health. Children with enamel hypoplasia are also at significantly greater odds for experiencing caries. Future research should include assessments of developmental defects of enamel to better understand the association between enamel hypoplasia and ECC.